Metode Inovasi Produk Dalam Meningkatkan Penjualan Produk Dezato Brownies - Dzar Algifari; Zakiyah Zahara; Syamsul Dg. Parani; Suryadi Samudra (Journal Economic Excellence Ibnu Sina, 2024)
In creating a product innovation is needed, in order to differentiate the product from its competitors and what makes the product far superior to other similar products. A company is required to be more innovative in producing a product so that it can attract consumers' interest in buying the product. The method used in this research is descriptive qualitative. This method focuses on problems based on facts carried out by observation, interviews, and studying documents. document. Bogdan and Taylor in Moleong (2010:04) state that qualitative research is "a research procedure that produces descriptive data in the form of written or spoken words from people and observable behavior". This research shows that creativity in developing innovation is very important to continue in the face of competition. The creativity of business actors plays a key role in creating products that are attractive in design. Innovations based on modulation, size, packaging, design and complementary materials implemented by Dezato Brownies have had a positive impact on their sales. This is caused by an increase in the number of market segments. Through product innovation, the use of various innovation sources, and effective marketing strategies, Dezato Brownies has succeeded in adapting to market dynamics and increasing consumer buying interest. Innovations such as modulation, sizing, packaging, design and complementary materials have had a positive impact on their sales by increasing product appeal and meeting evolving consumer needs.